Relationship of intraoperative perfusion parameters to the need for immediate extracorporeal support following heart transplantation. (October 2021) - Magruder, J Trent; Sperry, Alexandra; Atluri, Pavan; Bermudez, Christian; Cantu, Edward; Broniec, Gerald; Choi, Chloe; Acker, Michael A; Cevasco, Marisa
Purpose: We sought to assess the relationship of intraoperative perfusion parameters while on cardiopulmonary bypass, including oxygen delivery (DO2 ), to the need for ECMO following orthotopic heart transplantation (OHT). Methods: We included all adult (>18 years old) OHTs performed at our institution since implementation of an electronic perfusion record (March 2019-February 2020). Multi-organ transplants were excluded. The primary outcome was the need for immediate venoarterial ECMO in the OR following OHT. Univariable statistics were computed across demographic, clinical, operative, and perfusion variables, including oxygen delivery (DO2 ) measured each minute. Results: Fifty-three OHT were included with a median age of 54 years (interquartile range, 45-61). The primary outcome occurred in eight patients (15.1%). A significantly greater proportion of patients requiring ECMO had ischemic cardiomyopathy (50.0% (4/8) vs. 15.6% (7/45), p = 0.02) and had preoperative ventricular assist devices (37.5% (3/8) vs. 8.9% (4/45), p = 0.03). Median bypass times were longer in the ECMO group (217 vs. 147 minutes, p = 0.001). Phenylephrine doses were nonsignificantly higher in ECMO patients (4.1 vs. 1.9 mg, p = 0.10). No significant differences were observed in single-point median DO2 (275 vs. 294 mL O2 /min/m 2 BSA, p = 0.17) and nadir DO2 (226 vs. 222, p = 0.94), but increasing time and depth of DO2 below a threshold of 300 mL O2 /min/m 2 BSA (i.e. area over the DO2 curve (AOC) but below threshold) was significantly associated with the need for postoperative ECMO (p = 0.04). Conclusion: This is the first study to examine the relationship of perfusion parameters, including oxygen delivery, to outcomes following heart transplantation. We note that DO2 < 300-AOC was significantly associated with the need for postoperative ECMO following heart transplant. Further study will clarify whether potential DO2 differences in patients who require post-OHT ECMO reflect vasoplegia, or a more causative relationship which might be leveraged to improve outcomes.